Investigation on combustion, gaseous pollutants emission and ash characteristics during co-combustion of semicoke and coal slime. Issue 5 (October 2021) - Zhao, Ruidong; Dai, Ruowei; Chen, Tianju; Qin, Jianguang; Zhang, Jinzhi; Wu, Jinhu
Abstract: Co-combustion of semicoke and coal slime is promising for their co-disposal. In this study, the co-combustion behaviors, interaction and gaseous pollutants emission of semicoke and coal slime were studied by thermogravimetric analyzer coupled with Fourier transform infrared spectrometer (TG-FTIR). The ash characteristics after co-combustion were also investigated. Results showed adding coal slime could improve the ignition and burnout performance of blends but lead to the declining comprehensive combustion index. Inhibitory effects were prominent at the early stage of co-combustion due to the heat competition while promoting effects existed in fixed carbon combustion. The ash accumulation suppressed co-combustion again at the burnout stage. Semicoke could reduce NO, NO2 and SO2 emission of blends but also cause serious slagging because of the high Ca content. Adding coal slime could prevent the generation of eutectics and thus decrease the ash slagging propensity of blends. The sulfur-retention reaction was more intense at coal slime blend ratio of 40%. Semicoke ash had higher Mn, Ni and Cu concentrations while coal slime ash has more Zn and Pb contents. With the increase of coal slime blend ratios, Mn, Ni and Cu in ash gradually decreased while Zn and Pb increased. Graphical Abstract: ga1 Highlights: Ignition and burnout performance of semicoke are improved by blending coal slime. Different inhibitory and promoting effects exist at different co-combustion stage. NOx and SO2 emission of coal slime can be reduced by adding semicoke. Coal slime can significantly decrease the ash slagging propensity of semicoke.